Long Non-coding RNA Colon Cancer-Associated Transcript-1 Promotes Migration, Invasion, and Epithelial Mesenchymal Transition of Lung Adenocarcinoma by Suppressing miR-219-1 - Wang, Wenbo; Hou, Zhiliang; Wen, Chengcai; Ge, Liyue; Ge, Lili (Frontiers in Genetics, 2020)
Previous evidence suggests that long non-coding colon cancer-associated transcript-1(CCAT1) plays a pivotal role in the progression of a variety of tumors. However, little is known about its role in lung adenocarcinoma (LAD). In this study, we found LAD tissue samples had a higher expression of CCAT1 but a lower expression of miR-219-1 compared to their adjacent non-tumor tissues. CCAT1 negatively regulated the expression of miR-219-1. miR-219-1 suppressed the proliferation of A549 and H1299 cells. Knockdown of CCAT1 inhibited the proliferation, migration, and invasion of A549 and H1299 cells, which were reversed by the miR-219-1 inhibitor. CCAT1 knockdown increased the expression of E-cadherin but decreased the expressions of N-cadherin and vimentin, which were restored by the miR-219-1 inhibitor. In vivo, knockdown of CCAT1 suppressed the tumor growth of LAD xenografts, which were rescued by the inhibition of miR-219-1. In summary, our findings suggested that CCAT1 promotes the progression of LAD via sponging miR-219-1, providing a potential therapeutic target for LAD.